ARAH BARU PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH (Telaah Kurikulum dan Model Pembelajaran Pendidikan Agama Islam) (Pascasarjana IAIN Kudus, 2013)
Islamic Education subject (Pendidikan Agama Islam /PAI) at all levels of education geared toward learners realize that faithful,pious, and noble. To achieve this goal, we need to optimally PAI rolefunctionalization through revamping the curriculum and effectivelearning model and quality. PAI’s curriculum should be developedin a comprehensive manner, through three activities, namely : 1)strategic planning, 2) program planning, and 3) program deliveryplans. In addition, the implementation of the curriculum requiredan application-oriented method to value-oriented and in accordancewith the circumstances and character development-oriented studentsin learning subjects Islamic Education subject (Pendidikan AgamaIslam /PAI) itself.